How and when maternal viral infections can be a contraindication to breastfeeding: a narrative review - Alexandra Pimentel; Susana Pissarra; Gustavo Rocha; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2021)
The positive effects of breastfeeding on the health of infants and mothers are largely established. It is generally recommended that a mother should breastfeed exclusively for at least 6 months. Sometimes, however, this is not possible owing to a maternal disease. The purpose of this review was to understand the possibility and the mechanisms of transmission of viral agents to breastfed infants when the mother is infected and to evaluate whether and when breastfeeding can be harmful and, therefore, a real contraindication exists. In order to produce this narrative review, an extensive literature search was conducted on PubMed. The query included "breastfeeding", "mother to child" and "transmission" as keywords and a filter for publication date - from 2014 to 2019. Additionally, the bibliography of the selected articles was reviewed to identify further pertinent studies, which were then included. Only the following maternal infections were found to represent an absolute contraindication to breastfeeding: Human Immunodeficiency Virus and Human T-Lymphotropic Virus, because of their possible transmission via milk, and Ebola Virus, in which transmission to the child seems to be linked more to the close proximity relationship itself than the presence of the virus in human milk. Other viruses - Herpes Simplex Virus, Varicella Zoster Virus and Hepatitis C Virus - constituted a source of contraindication only in specific high-risk circumstances. To date, for the remaining viruses reviewed in this paper - including Severe Acute Respiratory Syndrome Coronavirus 2, no evidence exists that warrants contraindication of breastfeeding. Health professionals who deal with pregnant and puerperal women, such as obstetricians, pediatricians or family medicine doctors, must be aware of these particularities in the management of breastfeeding women in order to provide correct information and better take care of their patients and their respective infants.